Review of organic Rankine cycle for small-scale applications. (15th February 2017) - Rahbar, Kiyarash; Mahmoud, Saad; Al-Dadah, Raya K.; Moazami, Nima; Mirhadizadeh, Seyed A.
Highlights: Increasing demand for energy and environmental issues are biggest global challenges. Harnessing renewable energies and WHR can effectively address these issues. ORC is reliable technology that efficiently convert these heat sources into power. ORC application, working fluids, expanders, modelling and optimization are reviewed. Abstract: The ever-increasing demand for energy, scarcity of traditional energy sources and severe environmental issues are, perhaps, the biggest global challenges that need immediate actions. In this regard, harnessing the renewable energies and waste heat recovery are considered as potential solutions that can effectively address these issues. Organic Rankine cycle (ORC) is proved to be reliable technology that can efficiently convert these low to medium-grade heat sources into useful power. This paper is a comprehensive review of literature about the ORC that contains the ORC configurations, ORC applications, ORC working fluid selection and modelling and experimental study of the ORC expansion devices.